2014
DOI: 10.1590/1982-0216201414012
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do ruído na audição de trabalhadores de lavanderia hospitalar

Abstract: Conflict of interest: non-existentheadache, physiological changes in heart rate, blood pressure, sleep disorders, several digestive, vestibular, neurological and behavioral disorders such as irritability, tiredness, decreased productivity, noise intolerance, anguish, anxiety, depression, stress, among others 2,3 . In relation to the necessary time exposition for triggering noise-induced hearing loss, the highest number of impairing rates occurs between five and seven years, decreasing loss progression rate unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
3
0
5
Order By: Relevance
“…Outro estudo com usuários de estéreos pessoais com idade entre 16 e 29 anos que fazem uso constante de fones de ouvido identificou que 80% dos sujeitos tem pelo menos uma queixa auditiva: as mais referidas foram sensação de plenitude auricular, diminuição 2013;VIANA et al, 2013;FONTOURA et al, 2014;MENIN;KUNZ;BRAMATTI, 2014;DUARTE et al, 2015;OLIVEIRA et al 2015;POMMEREHN et al, 2016).…”
Section: Resultsunclassified
“…Outro estudo com usuários de estéreos pessoais com idade entre 16 e 29 anos que fazem uso constante de fones de ouvido identificou que 80% dos sujeitos tem pelo menos uma queixa auditiva: as mais referidas foram sensação de plenitude auricular, diminuição 2013;VIANA et al, 2013;FONTOURA et al, 2014;MENIN;KUNZ;BRAMATTI, 2014;DUARTE et al, 2015;OLIVEIRA et al 2015;POMMEREHN et al, 2016).…”
Section: Resultsunclassified
“…The specific scientific literature presents several studies on the development of interventions aimed at raising awareness of hearing protection in workers from different sectors, namely, (6,7) , carpentry (8) , hospitals (9,10) , civil defense -firefighters (11) , and food producing companies (12) . Hospital laundries, which are the object of the present study, are another occupational setting that presents risks to hearing (13) ; however, no studies describing educational actions in this segment have been observed. Studies conducted in hospital laundries found that noise in these places exceed the acceptable maximum level described in the Brazilian labor legislation for an 8-hour day's work (85 dBA).…”
Section: Introductionmentioning
confidence: 86%
“…Studies conducted in hospital laundries found that noise in these places exceed the acceptable maximum level described in the Brazilian labor legislation for an 8-hour day's work (85 dBA). According to these studies, the level of sound pressure observed in hospital laundries ranged from 85 to 101 dBA; they also reported that many workers did not make effective use of hearing protection devices (HPD) even though they were exposed to loud noise levels (13)(14)(15) . Therefore, the development of an awareness-raising educational practice is essential, that is, focused on development of critical consciousness of workers with respect to their health problems, stimulating the search for solutions and organization of collective action (4,16) .…”
Section: Introductionmentioning
confidence: 99%
“…Estudos revelam que ainda não houve redução dos riscos da surdez de origem ocupacional. 6 O termo "roupas hospitalares" é utilizado para diversos tipos de tecidos com diferentes cargas orgânicas e de microrganismos, utilizados tanto por pacientes quanto pelas equipes de saúde. Os tecidos são provenientes dos diversos setores de um hospital como maternidade, sala cirúrgica, banheiros, consultórios, roupas de funcionários (aventais, gorros e panos de limpeza) e dos quartos (fronhas, cobertores, toalhas, colchas, cortinas, roupas de pacientes etc.)…”
Section: Introductionunclassified